Effect of probiotic, prebiotic, synbiotic and medicinal plants on Carcass Characteristics, Immune organs, blood immunological parameters and blood Hematological and biochemical of broiler Fed on Different Levels of Protein - Kairalla مجدي; Aburas عبدالحكيم; Omar كريميان (Journal of Pure & Applied Sciences, 2022)
The purpose of this study was to see how non-antibiotic growth boosters such as Probiotic, Prebiotic, Synbiotic, and medicinal herbs (Mixture of Origanum majorana, Foeniculum vulgare, and Carum carvi in a 1:1:1 ratio) affected carcass yield, immune response, blood hematological, and biochemical parameters in broilers fed test diets with two dietary protein levels (normal and low). The research was conducted at Alexandria University, Poultry Research Center, Faculty of Agriculture. The trial lasted 42 days in total. A total of 500 one-day-old Cobb broiler chicks with similar average live body weight were assigned to one of ten treatment groups. Each treatment has five replicates with ten chicks each. Ten experimental diets were developed to be nearly is caloric and to provide all nutrients required for broiler growth throughout two stages of development: starter diets (1 - 21 days) and grower diets (22 - 42 days). Ten experimental diets were made up of five feed-additive programs and two amounts of crude protein (recommended or low, 85 percent of recommended) (control, probiotic, prebiotic, synbiotic and medicinal plants). Among the additives, synbiotic had a positive effect on the WBCs, RBCs, in general, especially the Fabricius bursa Under the conditions of the current study, synbiotic had a significant impact on hematological parameters, carcass yield, and immunological organs of broiler. Furthermore, more research is required to confirm the existing findings.